TEKNIK PASCA PANEN PAPRIKA (Capsicum annum var. grossum L) DI AGROWISATA PUNCAK BUKITCATU BEDUGUL-BALI: Post-Harvesting Technique of Paprica (Capcisum annum var. grossum L) at Bukitcatu Peak Agritourism, Bedugul Bali - Yasinta Wonga Ngandhe, Rosiana Ulfa, Bagus Setyawan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2021)
Fruit and vegetable commodities are very easily damaged when harvested because of the respiration and transpiration processes in the fruit. The most effective way to reduce respiration rate is by lowering the product temperature and packaging method. One way of packaging using plastic packaging. The selection of the thickness of the plastic packaging is critical because it is related to the permeability of the plastic to environmental conditions. The purpose of this fieldwork practice is to find out good post-harvest techniques for paprika plants in Agrowisata Puncak Bukit Catu Tabanan, Bali. The method used is a field study by collecting data through direct observation, namely direct interviews with all relevant parties, practice, and documentation, as well as literature study by taking data from the company and comparing it with theory. The result of this study are post-harvest handling of paprika commodities including sorting, namely separating damaged fruit, grading, namely separating paprika according to its size, washing, storing, packaging, and transporting.